Genome Sequencing of Xanthomonas vasicola Pathovar vasculorum Reveals Variation in Plasmids and Genes Encoding Lipopolysaccharide Synthesis, Type-IV Pilus and Type-III Secretion Effectors - Wasukira, Arthur; Coulter, Max; Al-Sowayeh, Noorah; Thwaites, Richard; Paszkiewicz, Konrad; Kubiriba, Jerome; Smith, Julian; Grant, Murray; Studholme, David J. (Pathogens, 2014)
Xanthomonas vasicola pathovar vasculorum (Xvv) is the bacterial agent causing gumming disease in sugarcane. Here, we compare complete genome sequences for five isolates of Xvv originating from sugarcane and one from maize. This identified two distinct types of lipopolysaccharide synthesis gene clusters among Xvv isolates: one is similar to that of Xanthomonas axonopodis pathovar citri (Xac) and is probably the ancestral type, while the other is similar to those of the sugarcane-inhabiting species, Xanthomonas sacchari. Four of six Xvv isolates harboured sequences similar to the Xac plasmid, pXAC47, and showed a distinct Type-IV pilus (T4P) sequence type, whereas the T4P locus of the other two isolates resembled that of the closely related banana pathogen, Xanthomonas campestris pathovar musacearum (Xcm). The Xvv isolate from maize has lost a gene encoding a homologue of the virulence effector, xopAF, which was present in all five of the sugarcane isolates, while xopL contained a premature stop codon in four out of six isolates. These findings shed new light on evolutionary events since the divergence of Xvv and Xcm, as well as further elucidating the relationships between the two closely related pathogens.
Keywords: Gumming disease; Sugarcane; Banana Xanthomonas wilt